Lactic acid bacteria in South African indigenous fermented milks and the evaluation of selected strains for application in the manufacturing of cultured milk - Bester, B.H. (University of Pretoria, 2013)
Dissertation (MSc Agric (Food Science))--University of Pretoria, 1999.